Perancangan Prototype ADGS Menggunakan Sensor Jarak Berbasis Arduino di Bandar Udara Djalaluddin Gorontalo - Fachrurrazi; Khoiruroziq, Fachri; Nilakresna, Sophia (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
Automatic Docking Guidance System (ADGS), a tool provided by the airport to help a pilot park his plane. Aircraft parking control activities at the airport, the pilot is assisted by a Marshaller who aims to direct the movement of the aircraft to the correct parking point. The increasingly dense activity of aircraft movement on the apron requires the use of alternative technology as a substitute for Marshallers, this technology is called the Automatic Docking Guidance System (ADGS, aircraft parking aids). The design of this ADGS prototype uses 2 Arduino UNO which are used as program language storage, 1 HC-SR04 proximity sensor to detect the presence or position of aircraft approaching the aircraft parking area or apron, and 1 infrared sensor to detect the movement of the aircraft moving to the right or to the right. to the left that are designed to be one so as to form a combination that matches the appearance of how ADGS works at Gorontalo Djalaludin Airport.